Perancangan Arsitektur Sistem dan Teknologi Informasi Menggunakan Togaf ADM (Studi Kasus Dinas Perhubungan Kota Balikpapan) - Soleh Ardiansyah; Adani Setiorini; Lovinta Happy Atrinawati; Tegar Palyus Fiqar (Universitas Bumigora, 2019)
Utilization of information systems or technology in an organization is needed to improve organizational efficiency. This relates to the rapid development of information systems or technology that affect the ongoing business processes. The effectiveness is in the form of aligning business strategy with information system strategy and business transformation. However, the dilemma faced especially in Government agencies such as the Balikpapan City Department of Transportation is how to align business strategies and information systems strategies that will be used so as to achieve organizational goals. Responding to the problem, it is necessary to align between the business needs of the organization and the needs of the application to support the vision and mission to be achieved by the Balikpapan City Department of Transportation. This can be achieved by using the framework of The Open Group Architecture Framework (TOGAF) which provides a detailed method of how to build, manage and implement an enterprise architecture known as the Architecture Development Method (ADM), hereafter referred to as TOGAF ADM. This research produces a mapping of business needs and application needs to support the vision and mission to be achieved through the information systems or technology architecture design including business architecture modeling, information system architecture, and technology architecture on the Balikpapan City Department of Transportation.